2021
DOI: 10.1155/2021/5565748
|View full text |Cite
|
Sign up to set email alerts
|

Gentiopicroside Produces Endothelium‐Independent Vasodilation by Deactivating the PI3K/Akt/Rho‐Kinase Pathway in Isolated Rat Thoracic Aorta

Abstract: Gentiopicroside (GPS), a main active secoiridoid glucoside derived from the roots of perennial herbs in the Gentianaceae family, has antispasmodic and relaxant effects. However, the vasorelaxant effects of GPS on aortic rings and the molecular mechanisms involved in these effects are not yet clear. Therefore, we investigated whether GPS inhibits phenylephrine- (PE-) or KCl-induced contractions in isolated rat thoracic aortic rings. The present study found that GPS produced a dose-dependent relaxation in aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The effects of NS on heart rate and contractility of isolated heart in the presence of calcium free Krebs solution have been observed in the past. 17 The isolated perfused hearts of Nigella treated rats showed the physiological cardiac hypertrophy in rats induced by long term NS supplementation, baseline peak tension and the maximum rate of tension development. 18 The bradycardia at low dose and tachycardia at high dose are related with the calcium channel blocking effects of NS as confirmed by various other studies.…”
Section: Resultsmentioning
confidence: 93%
“…The effects of NS on heart rate and contractility of isolated heart in the presence of calcium free Krebs solution have been observed in the past. 17 The isolated perfused hearts of Nigella treated rats showed the physiological cardiac hypertrophy in rats induced by long term NS supplementation, baseline peak tension and the maximum rate of tension development. 18 The bradycardia at low dose and tachycardia at high dose are related with the calcium channel blocking effects of NS as confirmed by various other studies.…”
Section: Resultsmentioning
confidence: 93%
“…Angiotensin, endothelin, NE, and other vasoconstrictors inhibit K ATP and K ir channels by activating Ca 2+independent or Ca 2+ -dependent PKC. [20][21][22][23][24]27 It is important to note that the K ATP channel is a Ca 2+ -independent potassium channel activated by PKC kinase. In this study, we observed that levosimendan induces vasorelaxation through inhibition of extracellular calcium influx.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unknown whether the activity of the inwardly rectifying potassium channel is regulated by levosimendan in the thoracic aorta. Studies have also shown that PKC kinases participate in vasodilation, and the activity of PKC is closely related to K ir , 20,21 K ATP channels, [22][23][24] and intracellular Ca 2+ levels. [20][21][22][23][24] Therefore, this study investigated the functional role of PKC-dependent K ir channels and the involvement of intracellular Ca 2+ in levosimendan-mediated relaxation in the vascular smooth muscle of the thoracic aortas of mice.…”
Section: Introductionmentioning
confidence: 99%
“…Gentiopicroside (GPS) is an iridoid glycoside isolated from the perennial herbs of Gentianaceae and is widely used in China as a herbal medicine for the treatment of rheumatoid arthritis, hemiplegia, joint pain, stroke, and hypertension (Xing et al, 2021). In addition, GPS has been found to exert antiinflammatory, anti-oxidant, and cholagogic pharmacological activities in all kinds of disease models (Wu et al, 2017;Li et al, 2018;Jin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%